High Thickness Tolerance in All‐Polymer‐Based Organic Photovoltaics Enables Efficient and Stable In‐Door Operation - Lei Zhang; Seonjeong Lee; Song Yi Park; Oskar J. Sandberg; Emily J. Yang; Paul Meredith; Yun‐Hi Kim; Ji‐Seon Kim (Advanced Science)
Abstract Organic photovoltaics (OPVs) have great potential to drive low‐power consumption electronic devices under indoor light due to their highly tunable optoelectronic properties. Thick devices (>300 nm photo‐active junctions) are desirable to maximize photocurrent and to manufacture large‐scale modules via solution‐processing. However, thick devices usually suffer from severe charge recombination, deteriorating device performances. Herein, the study demonstrates excellent thickness tolerance of all‐polymer‐based PVs for efficient and stable indoor applications. Under indoor light, device performance is less dependent on photoactive layer thickness, exhibiting the best maximum power output in thick devices (34.7 µW cm−2 in 320–475 nm devices). Thick devices also exhibit much better photostability compared with thin devices. Such high thickness tolerance of all‐polymer‐based PV devices under indoor operation is attributed to strongly suppressed space‐charge effects, leading to reduced bimolecular recombination losses in thick devices. The unbalanced charge carrier mobilities are identified as the main cause for significant space‐charge effects, which is confirmed by drift‐diffusion simulations. This work suggests that all‐polymer‐based PVs, even with unbalanced mobilities, are highly desirable for thick, efficient, and stable devices for indoor applications.